2001
DOI: 10.1007/s004230100216
|View full text |Cite
|
Sign up to set email alerts
|

Variations in complication rates and opportunities for improvement in quality of care for patients having abdominal aortic surgery

Abstract: In abdominal aortic surgery on patients in Maryland, the rates of some complications vary widely and are independently associated with increased in-hospital mortality and hospital charges (charges differ from costs). Efforts to reduce these complications should help to decrease both levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…[2][3][4] AKI is also a severe complication in general surgery, increasing mortality, morbidity and hospital costs. 5,6 Studies evaluating kidney function in abdominal aorta surgery demonstrated both glomerular (albuminuria) and tubular (increased urinary NAG-creatinine ratio) injury in up to 96% of the subjects, although only 22% had RIFLE-defined acute kidney injury, and a worse short-term (30 days) and long-term (10 years) survival of the AAA (abdominal aortic aneurysm) surgery patients who experienced a temporary AKI, even if their renal function completely recovered. 7,8 The aim of our study was to evaluate the prevalence of AKI, its association with the short-term (within 30-days postoperatively) and long-term (1 year postoperatively) prognosis in a cohort of patients with severe peripheral artery disease (PAD) undergoing surgical procedures of lower extremity revascularization or amputation and the most important comorbidities associated with AKI development.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] AKI is also a severe complication in general surgery, increasing mortality, morbidity and hospital costs. 5,6 Studies evaluating kidney function in abdominal aorta surgery demonstrated both glomerular (albuminuria) and tubular (increased urinary NAG-creatinine ratio) injury in up to 96% of the subjects, although only 22% had RIFLE-defined acute kidney injury, and a worse short-term (30 days) and long-term (10 years) survival of the AAA (abdominal aortic aneurysm) surgery patients who experienced a temporary AKI, even if their renal function completely recovered. 7,8 The aim of our study was to evaluate the prevalence of AKI, its association with the short-term (within 30-days postoperatively) and long-term (1 year postoperatively) prognosis in a cohort of patients with severe peripheral artery disease (PAD) undergoing surgical procedures of lower extremity revascularization or amputation and the most important comorbidities associated with AKI development.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with patients who are successfully extubated, patients who are reintubated have worse clinical outcomes, including prolonged lengths of stay (LOSs) in the intensive care unit (ICU) and hospital, and increased mortality [1-4]. The cause for the increased mortality is not known but has been hypothesized to be either a delay in reintubation or a complication of the endotracheal intubation itself.…”
Section: Introductionmentioning
confidence: 99%
“…As the data are primarily used for billing and administrative purposes, we could not quantify the severity of illness of patients. We identified complications associated with surgery using ICD-9-CM codes (Table e1) [10, 11]. Due to potential variation in use of the “present on admission” indicator, we chose not to use this indicator in generating complications, which is consistent with other studies [12].…”
Section: Methodsmentioning
confidence: 99%